2011
DOI: 10.1037/a0023995
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial resources, threat, and the perception of distance and height: Support for the resources and perception model.

Abstract: Threatening things are often perceptually exaggerated, such that they appear higher, closer, of greater duration, or more intense than they actually are. According to the Resources and Perception Model (RPM) psychosocial resources can prevent this exaggeration, leading to more accurate perception. Two studies tested RPM. Study 1 showed that the perceived closeness of a threatening object (a live tarantula) but not an innocuous object (a cat toy) was moderated by induced self-worth. Further, the more self-worth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 59 publications
9
66
0
Order By: Relevance
“…In particular, people should be biased to anticipate the motion of an approaching threat and misremember it as having come closer to themselves than it actually had. Indeed, related effects have been reported for spider stimuli (Cole, Balcetis, & Dunning, 2013;Harber, Yeung, & Iacovelli, 2011;Witt & Sugovic, 2013). Third, our displays of rings and dots on otherwise blank backgrounds were schematized, simple, and predictable in their content, and our predisplay descriptions conveyed threat only conceptually Hubbard, 1995Hubbard, , 2005Laney, Campbell, Heuer, & Reisberg, 2004;Laney, Heuer, & Reisberg, 2003;Vinson & Reed, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, people should be biased to anticipate the motion of an approaching threat and misremember it as having come closer to themselves than it actually had. Indeed, related effects have been reported for spider stimuli (Cole, Balcetis, & Dunning, 2013;Harber, Yeung, & Iacovelli, 2011;Witt & Sugovic, 2013). Third, our displays of rings and dots on otherwise blank backgrounds were schematized, simple, and predictable in their content, and our predisplay descriptions conveyed threat only conceptually Hubbard, 1995Hubbard, , 2005Laney, Campbell, Heuer, & Reisberg, 2004;Laney, Heuer, & Reisberg, 2003;Vinson & Reed, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting research perspective consists in extending the rationale of the economy-of-action account to social cognition. Recent evidence has suggested that this perspective is promising, since it has been reported that psychosocial resources and costs influence visual perception (Harber, Yeung, & Iacovelli, 2011;Morgado, Muller, Gentaz, & Palluel-Germain, 2011;Schnall, Harber, Stefanucci, & Proffitt, 2008; for reviews, see Balcetis & Lassiter, 2010;Schnall, 2011;Stefanucci, Gagnon, & Lessard, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the needs and motivations of the perceiver can influence their estimates of physical distance. People judged a threatening object (a live tarantula), but not an innocuous object (a cat toy), as physically closer (Harber, Yeung, & Iacovelli, 2011). However, the more self-worth that people reported, the farther away they estimated the tarantula, which led these authors to conclude that psychosocial resources play a role in judgments of physical distance (Harber et al, 2011).…”
Section: Distance Perceptionmentioning
confidence: 99%